THE EFFECT OF ENTERPRISE RISK MANAGEMENT (ERM), COMPANY PERFORMANCE, AND SIZE ON FIRMS’ VALUE - Miftakhul Fadhilah; Puji Sucia Sukmaningrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to determine the effect of Enterprise Risk Management (ERM), profitability, leverage, earnings per share and company size on firm value. The method used in this study is the Panel Data Regression with the study population of companies registered in the Jakarta Islamic Index between 2014-2018 period. The sample of this study consists of 13 companies and the data in this study were obtained from the company's annual report from the Indonesia Stock Exchange website. The results showed that profitability and leverage has a positive and significant effect on firm value. And Earning per Share has a negative and significant effect on company value. Meanwhile, Enterprise Risk Management and company size have no significant effect on firm value.Keywords:  firm value, enterprise risk management, profitability, leverage, earning per share, sizeREFFERENCE Aditya, O., & Naomi, P. (2017). Penerapan manajemen risiko perusahaan dan nilai perusahaan di sektor konstruksi dan properti. Esensi: Jurnal Bisnis Dan Manajemen, 7(2), 167–180. https://doi.org/10.15408/ess.v7i2.4981Agustina, L., & Baroroh, N. (2016). The relationship between Enterprise Risk Management (ERM) and firm value mediated through the financial performance. Review of Integrative Business and Economics Research, 5(1), 128–138.Ali, M. M., Hamid, N. S. A., & Ghani, E. K. (2019). Examining the relationship between enterprise risk management and firm performance in Malaysia. International Journal of Financial Research, 10(3), 239–251. https://doi.org/10.5430/ijfr.v10n3p239Ayuningsih, S. D., Sunarya, E., & Norisanti, N. (2019). Analisis keterkaitan return on equity dan earning per share terhadap nilai perusahaan pada PT. Astra Agro Lestari Tbk. Jurnal Bisnis Dan Manajemen, 6(1), 65–71.Brigham, E. F., & Houston, J. F. (2003). Fundamentals of financial management (Concise Fo). Florida: South-Western.Brigham, E. F., & Houston, J. F. (2004). Fundamentals of financial management (Tenth). Mason: Elm Street Publishing Service, Inc.Cheng, M.-C., & Tzeng, Z.-C. (2011). The effect of leverage on firm value and how the firm financial quality influence on this effect. World Journal of Management, 3(2), 30–53.COSO. (2004). Enterprise risk management- integrated framework executive summary.Ekaprastyana, D., & Anwar, S. (2017). The effect of earning per share and debt to asset ratio on firm’s value: Case study on food and beverage corporation listed in Indonesia Stock Exchange. Jurnal Keuangan Dan Perbankan, 13(2), 120–127.Endri. (2019). Determinant of firm’s value: Evidence of manufacturing sectors listed in Indonesia Shariah Stock Index. International Journal of Recent Technology and Engineering, 8(3), 3995–3999. https://doi.org/10.35940/ijrte.C5258.098319Endri, E., & Fathony, M. (2020). Determinant of firm’s value: Evidence from financial industry. Management Science Letters, 10(1), 111–120. https://doi.org/10.5267/j.msl.2019.8.011Erradiana, R., Ratih, A. E., & Ruwanti, S. (2015). Pengaruh current ratio, debt to equity ratio, earning per share, return on asset dan dividen payout ratio terhadap nilai perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode 2013-2015.Gujarati, D. N., & Porter, D. C. (2013). Dasar-dasar ekonometrika, buku 2, edisi 5. Jakarta: Salemba Empat.Harmono. (2009). Manajemen keuangan: Berbasis balanced scorecard pendekatan teori, kasus, dan riset bisnis. Jakarta: PT Bumi Aksara.Hoyt, R. E., & Liebenberg, A. P. (2011). The value of enterprise risk management. Journal of Risk and Insurance, 78(4), 795–822. https://doi.org/10.1111/j.1539-6975.2011.01413.xIswajuni, I., Manasikana, A., & Soetedjo, S. (2018). The effect of enterprise risk management (ERM) on firm value in manufacturing companies listed on Indonesian Stock Exchange year 2010-2013. Asian Journal of Accounting Research, 3(2), 224–235. https://doi.org/10.1108/ajar-06-2018-0006Iswajuni, Soetedjo, S., & Manasikana, A. (2018). Pengaruh Enterprise Risk Management (ERM) terhadap nilai perusahaan pada perusahaan manufaktur yang terdaftar di Bursa Efek. Journal of Applied Managerial Accounting, 2(2), 275–281. https://doi.org/10.30871/jama.v2i2.942Kayobi, I. gusti M. A., & Anggraeni, D. (2015). Pengaruh Debt to Equity Ratio (DER), Debt to Total Aset (DTA), dividen tunai dan ukuran perusahaan terhadap nilai perusahaan. Jurnal Akuntansi Dan Keuangan, 4(1), 100–120.Kholis, N., Sumarwati, E. D., & Mutmainah, H. (2018). Faktor-faktor yang mempengaruhi nilai perusahaan. Jurnal Analisis Bisnis Ekonomi, 16(1), 19–25.Li, Q., Wu, Y., Ojiako, U., Marshall, A., & Chipulu, M. (2014). Enterprise risk management and firm value within China’s insurance industry. Acta Commercii, 14(1), 1–10. https://doi.org/10.4102/ac.v14i1.198Marlina, T. (2013). Pengaruh earning per share , return on equity , debt to equity ratio dan size terhadap price to book value. Jurnal Ilmiah Akuntansi Kesatuan, 1(1), 59–72.Mindra, S., & Erawati, T. (2014). Pengaruh Earning per Share (EPS), ukuran perusahaan, profitabilitas dan leverage terhadap nilai perusahaan. Jurnal Akuntansi, 2(2), 10–22.Modigliani, M., & Miller, M. H. (1963). Corporate income taxes and the cost of capital: A correction. The American Economic Review, 53(3), 433–443.Mulyasari, D., Miyasto, & Muharam, H. (2013). Pengaruh enterprise risk management, firm size, leverage, sales growth, profitability terhadap firm value. Tesis tidak diterbitkan. Semarang: Universitas Diponegoro.Novari, P. M., & Lestari, P. V. (2016). Pengaruh ukuran perusahaan, leverage, dan profitabilitas terhadap nilai perusahaan pada sektor properti dan real estate. 5(9), 5671–5694.Noviana, C. K., & Nelliyana. (2017). Faktor-faktor yang mempengaruhi nilai perusahaan non keuangan yang terdaftar di Bursa Efek Indonesia. Jurnal Bisnis Dan Akuntansi, 19(3), 168–176. https://doi.org/10.34208/jba.v20i2.416Obradivich, J., & Gill, A. (2012). The impact of corporate governance and financial leverage on the value of american firms. International Research Journal of Finance and Economics, (91), 1–14. https://doi.org/10.12816/0034973Onggita, T. (2018). Pengaruh earning per share, struktur modal, struktur kepemilikan, profitabilitas dan ukuran perusahaan pada perusahaan manufaktur yang terdaftar di BEI tahun 2013-2016.Pamungkas, A. (2019). Pengaruh penerapan enterprise risk management (COSO) terhadap nilai perusahaan: Studi empiris pada perusahaan manufaktur yang terdaftar di BEI. Jurnal Akuntansi Maranatha, 11(1), 12–21. https://doi.org/10.28932/jam.v11i1.1539Pangaribuan, L. R. M., Sihombing, Y. R., Hasugian, S. S., & Purba, D. L. (2019). Pengaruh struktur modal, net profit margin, earning per share dan firm size terhadap price ti book value pada perusahaan sub sektor property dan real estate yang terdaftar di Indonesia Stock Exchange pada tahun 2014-1017. Jurnal Akrab Juara, 4(2), 39–49.Pesiwarissa, P., & Simu, N. (2014). Analisis pengaruh Debt to Equity Ratio (DER), Return on Equity (ROE) dan Earning per Share (EPS) terhadap nilai perusahaan. Jurnal Managemen, Akuntansi dan Studi Pembangunan, 13(2), 48–59.Rahmantio, I., Saifi, M., & Nurlaily, F. (2018). Pengaruh debt to equity ratio, return on equity, return on asset dan ukuran perusahaan terhadap nilai perusahaan. Jurnal Administrasi Bisnis, 57(1), 151–159.Rahmawati, A. D., Topowijono, & Sulasmiyati, S. (2015). Pengaruh ukuran perusahaan, profitabilitas, struktur modal dan keputusan investasi terhadap nilai perusahaan. Jurnal Administrasi Bisnis, 23(2), 1–7.Rizqia, D. A., Aisjah, S., & Sumiati. (2013). Effect of managerial ownership, financial leverage, profitability, firm size, and investment opportunity on dividend policy and firm value. Research Journal of Financing Accounting, 4(11), 120–130.Sanjaya, C. K., & Linawati, N. (2015). Pengaruh penerapan enterprise risk management dan variabel kontrol terhadap nilai perusahaan di sektor keuangan. FINESTA, 3(1), 52–57.Solikhah, D. R., & Hariyati. (2019). Pengaruh pengungkapan enterprise risk management terhadap nilai perusahaan dengan profitabilitas sebagai variabel mediasi. Jurnal Akuntansi Unesa, 6(3), 1–21.Suwardika, I. N. A., & Mustanda, I. K. (2017). Pengaruh leverage, ukuran perusahaan, pertumbuhan perusahaan, dan profitabilitas terhadap nilai perusahaan pada perusahaan properti. Manajemen Unud, 6(3), 1248–1277.Syafina, Dea Chadiza. (2018). Kebangkrutan Lehman Brother Memicu Krisis Ekonomi Global. https://tirto.id/kebangkrutan-lehman-brothers-yang-memicu-krisis-ekonomi-global-cYjMTahu, G. P., & Susilo, D. D. B. (2017). Effect of liquidity , leverage and profitability to the firm value (dividend policy as moderating variable) in manufacturing company of Indonesia Stock Exchange. Research Journal of Finance and Accounting, 8(18), 89–98.Tampubolon, M. P. (2004). Manajemen keuangan (finance management): Konseptual, problem, & studi kasus. Jakarta: Penerbit Ghalia Indonesia.Weston, J. F., & Copeland, T. E. (1999). Manajemen keuangan. Jakarta: Penerbit Erlangga.